Automatic Liquid Filling Machine using Flow Sensor and Arduino Pro Mini - Rahmad Hidayat; Handayani Saptaji Winahyu (Indonesian Journal of Engineering Research, 2020)
The Small Industries Enterprise (SME), which is especially involved in the liquid filling industry (such as mineral water, tea, liquid milk, juice, etc.), needs some device that has the ability to measure liquid automatically and accurately into some container. Based on the 'Water Fall' method, this study carries out a procedure for making compact and efficient tools ('requirements definition' stage), using a keypad start button, flow sensor, temperature sensor, fan, buzzer, LCD 1602, relay driver ('system & software design' stage), implement a schematic drawing of the circuit and install all hardware inside the casing ('implementation and unit testing' stage), install accessories, set parameters and volume target ('integration and system testing ' stage) and re-calibrate the device ('operation and maintenance' stage). After the measurement experiment, we got that Fillco (the name of the device) has a bigger error for measurement below 1000 ml (0.6-15%) and better accuracy measurement for targeted volume upper than 1000 ml (0.04-0.20%). Fillco also able to memorize and reset liquid volume.